ANALISIS PENGARUH INVESTASI PMA, PMDN, NILAI PRODKSI DAN UNIT USAHA TERHADAP PENYERAPAN TENAGA KERJA SEKTOR INDUSTRI MANUFAKTUR DI PROVINSI JAWA TIMUR - DEWI, LINDA KURNIA; GUNAWAN, KUNTO INGGIT (JEB17 : Jurnal Ekonomi dan Bisnis, 2018)
ABSTRACTThe-purpose-of-this-study-is-to (1) find out how much influence the amount of investment PMA, PMDN, Production Value and Business Unit to the absorption of labor industry manufacturing in eastern Java province partially and (2) know how much influence the amount of investment PMA, PMDN, Production and Business Unit to the absorption of manpower of manufacturing industry of East Java province simultaneously. The theory used in this research is the theory related to the absorption of labor. The data collected in the form of secondary data coherent time from 2010 to 2017 and then analyzed by using multiple regression. The result of the research shows (1) The amount of PMA investment has negative effect on the absorption of manpower, while the investment variable of PMDN has a significant effect on the absorption of manpower. (2) Investment of PMA, PMDN, Production Value and business unit simultaneously influence to the absorption of labor force of manufacturing industry in east java. Influence of independent variable to dependent variable equal to 98,7,3% while the rest equal to 1,3% influenced by other variable not examined in this research.Â Keywords: Total Investment, Production Value, Business Unit and Labor,